PENERAPAN ASAS PERADILAN CEPAT, SEDERHANA DAN BIAYA RINGAN DALAM PEMERIKSAAN PERKARA DISPENSASI NIKAH - Endang Eko Wati; Rakhma Nurrozalina; Ari Tri Wibowo (Faculty of Social, Economics and Humanities, 2021)
Many factors lead people to get married even though their age do not meet the requirement of the Marriage Law. It happens because they desire to avoid the adultery tradition or probably their mate is being pregnant. It becomes problem when people who are under nineteen years old involve to this issue. They actually require additional legal consideration and the existence of legal certainty regarding to the abridge pace of the registration offer until the presence of establishment. The invocation proposes by the parents are for the sake of their children. By mean of these, this study aimed to investigate the practice of principles such as a brief, simple and low-cost toward the case of a marriage dispensation petition through the ethic Contante Justitie. This study used the empirical juridical approach to gain the facts from the implementation of Contante Justitie, and this study belongs to descriptive qualitative research. The data were collected from primary data supported by secondary data. The data gathered from official document, literature, and the results of unstructured interview. Then, the results are presented through texts and qualitative descriptive analysis. The result has indicated that the basis principles of Contante Justitie has implemented in surroundings religious court in Purwokerto. It is useful to protect underage marriage due to the pressing reasons to get married.